Teacher’s Professional Role In Improving The Learning Process - Muhammad Solih; Alfi Hafifah Habibah; Ayu Putri Julia (Universitas Muhammadiyah Enrekang, 2022)
In this study, the author took the title The Professional Role of Teachers in Improving the Learning Process, for this we both know that the teacher is an important figure in an educational institution. His role as a teacher and educator makes him a highly respected figure for everyone. The professional role of teachers in improving the learning process is also inseparable from how much competence they have. The better the competencies he has, the better the learning process that takes place in the classroom. The position of the teacher as a professional is intended to function to increase the dignity and the role of the teacher as a learning agent to improve the quality of education and national education. The position of teachers as professionals aims to implement the national education system, namely the development of the potential of students to become human beings who believe and fear God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent, and become democratic and responsible citizens,answer.